Deaths Due to Hanging: A Retrospective Autopsy Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Hanging is one of the most common methods of committing suicide all around the world. This is retrospective study conducted between Jan 2018 to December 2022, which included 48 cases of Hanging which were autopsied in Mortuary of Bhagat Phool Singh Government Medical College for Women, Khanpur Kalan, Sonipat, Haryana during this period. Out of 48 cases of Hanging, 34 (70.8%) cases were males and 14 (29.2%) cases were females. Maximum number of victims 16 (33.3%) were in the age group of 21-30 years. Maximum 42 (87.5%) cases occurred in closed place and least number of cases occurred in open place 06 (12.5%). Cyanosis was seen in around 43(89.5%) of cases and face congestion seen in around 24 (50%) cases. Ligature mark present above the level of thyroid cartilage in maximum number of cases 43 (89.5%). Fracture of hyoid bone present in 6 (12.5%) cases. Aim of the study was to find out incidence, trends and patterns of hanging in Haryana.
Keywords: Hanging; Cyanosis; Ligature mark; Autopsy; Suicide.